1961
DOI: 10.1152/ajplegacy.1961.200.6.1345
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of zinc-65

Abstract: The absorption, deposition, and excretion of zinc65 was studied in mice, rats, and dogs. When zinc65 was fed to the animals it was poorly absorbed, but its long biologic half-life made even the small portion absorbed physiologically significant. Absorption was obviated by feeding large quantities of nonradioactive carrier zinc. Injected zinc65 chloride first was deposited, preferably in the pancreas, liver, and spleen, with only minor deposition in muscle and in the brain. Subsequently, a large proportion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

1963
1963
2000
2000

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…McDonald et al (1966) presented the zinc concentration in the animal body along with other essential elements (Table 9). Sheline et al (1943) and Rubini et al (1961) found 65 Zn injected in the mouse and dog was accumulated first in the liver, pancreas and spleen, with later transfer to bone, skin, and skeletal muscles. As liver, pancreas, spleen and kidney tissue declined in 65 Zn activity, other tissues slowly began to accumulate radioactive zinc.…”
Section: "Zn Tissue Distribution and Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…McDonald et al (1966) presented the zinc concentration in the animal body along with other essential elements (Table 9). Sheline et al (1943) and Rubini et al (1961) found 65 Zn injected in the mouse and dog was accumulated first in the liver, pancreas and spleen, with later transfer to bone, skin, and skeletal muscles. As liver, pancreas, spleen and kidney tissue declined in 65 Zn activity, other tissues slowly began to accumulate radioactive zinc.…”
Section: "Zn Tissue Distribution and Transportmentioning
confidence: 99%
“…Absorption of 65 Zn from the gastro-intestinal (G.I.) tract generally is low, but due to its long biological half life small assimilated quantities are of physiological significance (Rubini et al, 1961). In attempting to learn more of the role of zinc in the metabolism of vertebrates, much laboratory work has been carried out on chicks (Roberson and Schaible, 1958;Rahman et al, 1959;Kienholz et al, 1964;Turk, 1963Turk, , 1964and Ziegler et al, 1964), rats (Stirn, 1935;Feaster et al, 1955;Ballou, 1958Ballou, , 1960Taylor, 1961;, and mice (Sheline et al, 1943;Cotzias et al, 1962;and Richmond etal., 1962).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported either relatively short (a few weeks) or long (several months) half-lives of zinc in both mammals and "sh, depending on the test species and experimental design (Rubini et al, 1961;Shulman et al, 1961;Andermann and Dietz, 1982;Alsop et al, 1999). For example, whole-body measurements of the half-life of Zn in small "sh range from 13 days in silversides Menidia menidia (Shulman et al, 1961) to greater than 6 months in mosquito"sh Gambusia holbrooki ( formerly, G. a.nis) (Willis and Jones, 1977;Newman and Mitz, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian species, zinc initially accumulates in the liver, kidney, pancreas, and spleen within the "rst 2 to 24 h of exposure and then is redistributed to bone (Gregus and Klaasen, 1986;Hammond and Beliles, 1980;Rubini et al, 1961;Guillard et al, 1984). Intravascularly (iv) administered zinc in rats was primarily excreted in the feces (31% of dose) during the "rst 4 days of elimination, and renal and biliary excretion were minor ( 42% of dose) (Gregus and Klaassen, 1986).…”
Section: Introductionmentioning
confidence: 99%